2019
DOI: 10.1155/2019/8573182
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Energy Production in the Deep Carbonate Geothermal Reservoir by Wellbore-Reservoir Integrated Fluid and Heat Transport Modeling

Abstract: Geothermal energy is clean and independent to the weather and seasonal changes. In China, the huge demanding of clean energy requires the geothermal energy exploitation in the reservoir with depth larger than 1000 m. Before the exploitation, it is necessary to estimate the potential geothermal energy production from deep reservoirs by numerical modeling, which provides an efficient tool for testing alternative scenarios of exploitation. We here numerically assess the energy production in a liquid-dominated mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Crooijmans et al (2016) considered the impact of heterogeneity on energy extraction for a low-temperature geothermal doublet system. Permeability and porosity heterogeneity greatly affected CO 2 migration (Xu et al, 2017;Wang et al, 2019) and the produced water temperature and heat recovery (Li et al, 2019). Pandey et al (2015) showed the influence of reservoir permeability heterogeneity during geothermal heat extraction.…”
Section: Parametersmentioning
confidence: 99%
“…Crooijmans et al (2016) considered the impact of heterogeneity on energy extraction for a low-temperature geothermal doublet system. Permeability and porosity heterogeneity greatly affected CO 2 migration (Xu et al, 2017;Wang et al, 2019) and the produced water temperature and heat recovery (Li et al, 2019). Pandey et al (2015) showed the influence of reservoir permeability heterogeneity during geothermal heat extraction.…”
Section: Parametersmentioning
confidence: 99%
“…(9)-( 11) formulas were applied universally to calculate the fluid inflow to the wellbottom and gas condensate mix-ture evacuation through the well PT. Model of the formulas was selected for nonadiabatic expansion of the fluid migra-tion according to a concept applied for natural gas migration with heat exchange via depth oil-and-gas pipelines [12], [13]. The authors added K a parameter taking into consideration the process deviations from adiabatic conditions.…”
Section: Development Of the Mathematical Modelmentioning
confidence: 99%
“…Hydraulic resistance within production tubing or within any other tubing of λ well is a function of Re number, temperature, and other standard parameters and design parameters [11]; hence, in the context of the research of nonisothermal lifting of hydrocarbon mixture, the working functional dependence λ (P, T, M, M q , D, k e ) has been developed and applied for equation (7). The dependence is based upon Colebrook-White equation and S. Borisov and I. Khodanovich studies [12] (instead of the abovementioned functional dependence λ (k e , Re, D)):…”
Section: Development Of the Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we chose T2Well simulator to simultaneously calculate the flow in both the wellbore and in the reservoir; this simulator was developed by Pan and Oldenburg (2014) to solve the problem of nonisothermal flows in an integrated wellbore-reservoir system; it has been verified against an analytical solution of steady-state two-phase flow and field CO 2 production test data. In the recent years, T2Well has been widely applied for productivity forecasting of geothermal doublet systems (Feng et al., 2017; Li et al., 2019; Xu et al., 2017) and the interpretation of production tests in geothermal wells (Vasini et al., 2018).…”
Section: Introductionmentioning
confidence: 99%